Supervisão de ensino: estudo descritivo de atos normativos e discussão de termos de visita/acompanhamento - Ferreira, Claudicéia Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This dissertation discusses a descriptive study of normative acts from the 1950s to the present day, governing responsibilities, professional profile, skills and professional skills of the Department the State of Education of São Paulo-SEESP called Teaching Supervisor. This study investigates the characteristic document of professional assignment, Supervisor Teaching, prepared by their school visits, called Terms of Business / Monitoring - TVA. The rules determining the Supervisor Teaching in the school supervision and inspection includes observation in administrative, educational, physical and materials, with a view to advice, guidance and evaluation. In Teaching Regional- DER Board, the place where the Teaching Supervisor is allocated by the skills to provide advice, guidance and monitoring of the planning, development and evaluation of teaching and learning in public and private schools, with reference to reality schools, educational theories and practices and the relevant legal standards to national education and basic education offered by the State education System. We sought to establish the relationship between the normative acts and sample Terms of Business / Monitoring relating to schools in the public schools, a Board Regional Education. Held the categorization of actions listed in the Terms of Business / Monitoring to identify elements of Teaching Supervisor duties related to administrative and pedagogical aspects. Search the elucidation of supervisory practice in reflexive perspective possible to understand the role of this professional qualification with purpose of the educational process, in which the Supervisor Teaching takes the partnership with school administrators, teachers and school community in the building process of educational excellence. It is expected that this dissertation contributes to the reflection about the importance of records, visit Terms of / Monitoring as an official document, advancing the ...

Essa dissertação debruça-se de forma descritiva sobre os atos normativos, da década de 1950 até os dias atuais, que regem as atribuições, o perfil profissional, as competências e as habilidades do profissional da Secretaria de Estado da Educação de São Paulo-SEESP, denominado Supervisor de Ensino. Esse estudo investiga o documento característico da atribuição profissional do Supervisor de Ensino, elaborado mediante suas visitas escolares, denominado Termo de Visita/Acompanhamento-TVA. A determinação normativa do Supervisor de Ensino no âmbito escolar de supervisão e fiscalização compreende a observação dos aspectos administrativos, pedagógicos, físicos e materiais, com vistas ao assessoramento, orientação e avaliação. Ao Supervisor de Ensino, alocado na Diretoria de Ensino Regional-DER, compete prestar assessoria, orientação e acompanhamento do planejamento, desenvolvimento e avaliação do ensino e da aprendizagem nas escolas públicas e particulares, tendo como referência a realidade das escolas, as teorias e práticas educacionais e as normas legais pertinentes à educação nacional e à educação básica oferecida pelo Sistema de Ensino Estadual. No presente trabalho, buscou-se estabelecer relação entre os atos normativos e amostras de Termos de Visita/ Acompanhamento, relativos a escolas da rede pública estadual, de uma Diretoria de Ensino Regional. Realizou-se a categorização de ações, elencadas nos Termos de Visita/ Acompanhamento para identificação de elementos das atribuições do Supervisor de Ensino relacionadas aos aspectos administrativos e pedagógicos. Assim, buscou-se a elucidação da prática supervisora, em perspectiva reflexiva, possibilitando uma maior compreensão das atribuições deste profissional, com a finalidade de qualificação do processo educacional, onde o Supervisor de Ensino assume a parceria com os gestores escolares, docentes e comunidade escolar, no processo de ...
Keywords: Educação; Supervisores escolares; Professores - Avaliação; Education